A Historically Based Review of Empirical Work on Color and Psychological Functioning: Content, Methods, and Recommendations for Future Research. Issue 2 (June 2019) - Elliot, Andrew J.
Empirical work on color and psychological functioning has a long history, dating back to the 19th century. This early research focused on five different areas: Arousal, physical strength, preference, time perception, and attention. In the present paper, I overview the relations observed in this early research, and detail methodological weaknesses therein. I then trace subsequent 20th and 21st century developments in these research areas, in terms of both content and methods. Finally, I extend the review to cover the full breadth of research in this domain of inquiry, and provide guidelines for interpreting existing work and conducting future work. Thus, this historically based review tells us much about research on color and psychological functioning, including where it started, where it has been, where it is, and where it can go.